PENGARUH KERAGAMAN PRODUK, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP MINAT BELI ULANG DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA APOTEK RABELLA FARMA PANARUKAN - Nova Berliyanti Ramadani; Lusiana Tulhusnah; Yudha Praja (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The strategies implemented by companies in marketing their products to the public are key factors that influence customer satisfaction. Given the diverse needs of society, companies must be able to analyze and prepare appropriate strategies to meet consumer expectations. This study aims to analyze the influence of product diversity, product quality, and service quality on repurchase intention, with customer satisfaction as an intervening variable at Rabella Farma Pharmacy Panarukan. The study involved 99 respondents who were selected using simple random sampling. Data analysis and hypothesis testing were conducted using the Structural Equation Modeling–Partial Least Squares (PLS-SEM) approach with SmartPLS 3.0 software. The direct effect hypothesis testing results show that product diversity has a negative but insignificant effect on customer satisfaction; product quality has a positive but insignificant effect on customer satisfaction; and service quality has a significant positive effect on customer satisfaction. Furthermore, product diversity has a negative but insignificant effect on repurchase intention; product quality has a positive but insignificant effect; and service quality has a significant positive effect on repurchase intention. Customer satisfaction has a significant positive effect on repurchase intention. Regarding indirect effects, product diversity and product quality have no significant effect on repurchase intention through customer satisfaction, while service quality has a significant positive effect on repurchase intention through customer satisfaction.